Tourism Communication in The Development of Sustainable Intelligent Tourism Village in East Lombok As A Supporting Area for Mount Rinjani Global Geopark and Mandalika - Edy Prihantoro; Rio Setia Monata; Yusuf Maulana; Atit Pertiwi; Suryarini Widodo; Rizky Wulan Ramadhani (Ikatan Sarjana Komunikasi Indonesia, 2022)
The development of Indonesian tourism after the Covid-19 pandemic began to rise again. Various efforts have been made by the government and tourism actors to be able to revive the tourism sector. The purpose of this study is to analyze tourism communication in the development of a Sustainable Smart Tourism Village in East Lombok as a supporting area for Mount Rinjani Global Geopark and the Mandalika Special Economic Zone. This study uses a qualitative descriptive method by conducting interviews and direct observations of Loyok Village. The data collected were analyzed using data analysis techniques from Miles Huberman. The results of the study indicate that the development of a sustainable smart tourism village in East Lombok requires collaboration from various parties such as the government, tourism actors, communities, and researchers all at once. The Gunadarma University Matching Fund team is here to help implement five information and communication technologies (ICT) in tourist villages such as making smart homestays, making virtual reality videos, and QR Codes, making new designs for bamboo crafts, and tourist village websites. The application of this technology is also part of communication and is expected to support the development of Loyok Tourism Village in East Lombok Regency. The implementation of ICT in East Lombok Regency is also expected to serve as a pilot project in the development of smart homestays in Indonesia.